Potential use of smartphone as a tool to capture embryo digital images from stereomicroscope and to evaluate them by an artificial neural network - De Souza Ciniciato, Diego [UNESP]; Takahashi, Maria Beatriz [UNESP]; Gouveia Nogueira, Marcelo Fábio [UNESP]; Rocha, José Celso [UNESP] (My University, 2017)
An online graphical user interface connected to a server was developed aiming to facilitate access to professionals worldwide that face problems with bovine blastocysts classification. The blastocysts assessment is carried on using images taken from an inverted microscope, which usually requires more expensive devices such as digital camera and computer software. Smartphone camera quality and tasks processing are getting better with technology advances. Therefore, a smartphone can be attached to the eyepiece lens to provide Real-Time evaluation, and thus reducing costs when comparing to computers, cameras, and software that are commonly used for this purpose.
Keywords: Artificial Neural Network-based Software; Embryo Classification; Graphic User Interface; Smartphone